Market Place Solution To Trade Problems In Pandemic Times - Ulfatun Nikmah (Jurnal PKM Manajemen Bisnis, 2021)
The difficulty in the pandemic period, forcing all humans to improve the ability to survive, is no exception in the business sector. Not a few small and medium businesses have gone out of business due to the Covid 19 outbreak. This needs to be addressed wisely and intelligently, one of which is by utilizing online sales on the digital market or known as the Market place. Facts show, since the pandemic, online sales trends are more popular, because activity restrictions are enforced. Of course, this is an opportunity that can be used to overcome the problem of declining direct sales. This activity is intended to provide skills training to participants in community service activities, namely upper-level students, to be able to use the digital market as a basis for selling products in the era of globalization. This activity is carried out using the method of material explanation, practice, and discussion. Explicitly, this activity increases participants' knowledge and makes them aware of the opportunities to sell digitally, by utilizing the marketplace.